Formulation and Characterization of Blend Microspheres of Dexrabeprazole - Thakur, Sanju; Banke, Abhishek; Singh, Shikha; Jain, Nilesh; Goswami, R.B. (Journal of Neonatal Surgery, 2025)
Dexrabeprazole blend microspheres were developed using a solvent evaporation technique to achieve controlled drug release for therapeutic applications. The microspheres were prepared by emulsifying a polyblend solution of polylactic acid (PLA) and polycaprolactone (PCL) in a polyvinyl alcohol (PVA) solution. The formulations were evaluated for their percentage yield, entrapment efficiency, flow properties, stability in acidic conditions, and drug release profiles. Among the formulations, F3 showed the highest entrapment efficiency (82.25%) and an optimal drug release profile with a slow, sustained release over 12 hours. Scanning electron microscopy (SEM) revealed spherical, smooth microspheres, indicating well-formed drug carriers. The drug release followed zero-order kinetics, demonstrating the potential of the microspheres for prolonged drug release. The results suggest that the blend microspheres of Dexrabeprazole are suitable for controlled release applications, improving therapeutic efficacy and patient compliance.